2007
DOI: 10.1063/1.2749177
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial approach to thin-film transistors using multicomponent semiconductor channels: An application to amorphous oxide semiconductors in In–Ga–Zn–O system

Abstract: A combinatorial approach was applied to thin-film transistors (TFTs) using amorphous In–Ga–Zn–O semiconductor channels. A large number of TFTs, having n-type channels with different chemical compositions, were fabricated simultaneously on a substrate. A systematic relation was clarified among the compositional ratio of In:Ga:Zn, oxygen partial pressure in film deposition atmosphere, and TFT characteristics. The results provide an experimental basis to understand the roles of each metallic element in the In–Ga–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
180
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(190 citation statements)
references
References 14 publications
6
180
0
2
Order By: Relevance
“…For room temperature-fabricated AOS TFTs, Canon fi rst succeeded in fabricating a-IGZO TFTs by radiofrequency (RF) magnetron sputtering [48]. Combinatorial approaches have been employed to screen multi-component AOS systems, including the In-Ga-Zn-O system [49] and Zn-Sn-O (ZTO) system [50]. Other materials, such as a-In-Zn-O (a-IZO) [51], a-In-Ga-O (a-IGO) [14] and a-Ga-Sn-Zn-O (a-GTZO) [52], have also been reported.…”
Section: Materials and Processesmentioning
confidence: 99%
“…For room temperature-fabricated AOS TFTs, Canon fi rst succeeded in fabricating a-IGZO TFTs by radiofrequency (RF) magnetron sputtering [48]. Combinatorial approaches have been employed to screen multi-component AOS systems, including the In-Ga-Zn-O system [49] and Zn-Sn-O (ZTO) system [50]. Other materials, such as a-In-Zn-O (a-IZO) [51], a-In-Ga-O (a-IGO) [14] and a-Ga-Sn-Zn-O (a-GTZO) [52], have also been reported.…”
Section: Materials and Processesmentioning
confidence: 99%
“…Amorphous oxide semiconductors such as In-Ga-Zn-O, [1][2][3][4] In-Zn-O, 5,6 Zn-Sn-O, [7][8][9][10] In-Sn-O, 11 and In-Zn-Sn-O 12,13 have attracted considerable attention as channel materials for next-generation thin-film transistors (TFTs). Compared with crystalline materials, amorphous oxide materials have advantages because of their low processing temperatures and uniformity of device characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…29 It has been reported that the roles of indium and gallium are related to the mobility and off-current leakage, respectively. 33,34 In addition, zinc affects the S.S., modulation of the shallow tail state and reduction of interstitial states at the interface. 34,35 For this reason, the concentration ratio of each component in the film plays a significant role in determining the device performance of TTFTs.…”
Section: Methodsmentioning
confidence: 99%
“…33,34 In addition, zinc affects the S.S., modulation of the shallow tail state and reduction of interstitial states at the interface. 34,35 For this reason, the concentration ratio of each component in the film plays a significant role in determining the device performance of TTFTs. Hafnium possesses an atomic radius close to that of indium and is easily bonded with oxygen resulting in lower carrier concentration sensitivity, which improves the device performance.…”
Section: Methodsmentioning
confidence: 99%